2013
DOI: 10.3390/molecules18033279
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions of Oxygen with Small Gold Clusters on Nitrogen-Doped Graphene

Abstract: By means of density functional theory, the adsorption properties of O 2 molecule on both isolated and N-graphene supported gold clusters have been studied. The N-graphene is modeled by a C 65 NH 22 cluster of finite size. The results indicate that the catalytic activity and the O 2 adsorption energies of odd-numbered Au clusters are larger than those of adjacent even-numbered ones. The O 2 molecule is in favor of bonding to the bridge sites of odd-numbered Au clusters, whereas for odd-numbered ones, the end-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Those values are comparable with our values. Notice that in our case we have used 1 polarization function extra in the basis with respect to the case of ref (PW91/TZP level). Additionally, the relativistic correction method is introduced in the Hamiltonian (ZORA), while in the ref is not the case.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those values are comparable with our values. Notice that in our case we have used 1 polarization function extra in the basis with respect to the case of ref (PW91/TZP level). Additionally, the relativistic correction method is introduced in the Hamiltonian (ZORA), while in the ref is not the case.…”
Section: Methodsmentioning
confidence: 99%
“…63,64 The Au 7 average bond length (see Appendix 2 of the Supporting Information for its Cartesian coordinates) is 2.6958 Å, and its LUMO−SOMO (lowest unoccupied molecular orbital minus single occupied molecular orbital) gap is 0.973 eV. Since there are not available experimental data on these quantities, we compare them with theoretical descriptions of other researchers: The values for the Au 7 average bond length are (a) 2.69 Å, at BLYP/DNP level of theory with scalar relativistic corrections (see details in ref 65) and (b) 2.722 Å, at PW91/ TZP level of theory, with scalar relativistic effects (see details in ref 66) At the same levels of theory, the SOMO-LUMO gap are 1.07765 and 1.00 eV,66 respectively. Those values are comparable with our values.…”
mentioning
confidence: 99%
“…The AuNPs-NGODs catalyst exhibited higher removal efficiency among various catalysts, such as with Pt/Rh nanoparticles (347 mg·g –1 ), carbon-Pt self-assembled nanocomposites (196 mg·g –1 ), Ni/porous carbonCNT (312 mg·g –1 ), PdNP-activated carbon (75.4 mg·g –1 ), and more, as shown in Figure S5. Additionally, the prepared AuNPs-NGODs hybrid catalyst was tested up to three reusable cycles with around 10% change in the catalytic MB degradation activity as compared with the 0th cycle.…”
Section: Resultsmentioning
confidence: 97%
“…[25] DFT calculations have suggested that hybridization of Au with graphene materials can result in a highly active and stable ORR electrocatalyst. [40,41] Therefore, there is an emerging interest to develop AuNCs-based nanocomposites using graphene-related materials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, aggregation of AuNCs is prevented due to the strong metal support interaction between rGO and metal clusters [25] . DFT calculations have suggested that hybridization of Au with graphene materials can result in a highly active and stable ORR electrocatalyst [40,41] . Therefore, there is an emerging interest to develop AuNCs‐based nanocomposites using graphene‐related materials.…”
Section: Introductionmentioning
confidence: 99%